A Comparative Evaluation of Recurrence Rates, Urinary Flow Improvement, and Patient-Reported Outcomes following Endoscopic Urethrotomy Versus Open Urethroplasty for Anterior Urethral Strictures - Muhammad Seerwan, Muhammad Ilyas, Muhammad Adnan, Ibrar Ahmad, Saifullah, Ali Shandar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anterior urethral stricture disease is a common urological condition causing lower urinary tract obstruction, recurrent infections, and reduced quality of life. Management options include endoscopic urethrotomy and open urethroplasty, yet comparative data on recurrence, urinary flow, and patient-reported outcomes remain limited. Objective: To compare recurrence rates, urinary flow improvement, and patient-reported outcomes following endoscopic urethrotomy versus open urethroplasty for anterior urethral strictures. Methods: This prospective observational study was conducted at Department of Urology Gomal Medical College, DI Khan, from November 2022 to July 2023. A total of 160 male patients were enrolled: 80 underwent endoscopic urethrotomy (Group A) and 80 underwent open urethroplasty (Group B). Preoperative evaluation included uroflowmetry, retrograde urethrogram, and patient-reported outcomes using the International Prostate Symptom Score (IPSS) and quality-of-life measures. Patients were followed at 1, 3, 6, and 12 months. Primary outcome was stricture recurrence; secondary outcomes included maximum urinary flow rate (Qmax), symptom scores, and complications. Results: Baseline demographics were comparable, though stricture length was longer in the urethroplasty group (2.8 ± 0.9 cm vs 1.4 ± 0.5 cm, p<0.001). Recurrence at 12 months was significantly higher after endoscopic urethrotomy (45%) compared to urethroplasty (12.5%, p<0.001). Qmax improved in both groups, but sustained improvement favored urethroplasty (20.2 ± 4.8 ml/s vs 12.9 ± 4.5 ml/s, p<0.001). Patient-reported outcomes, including IPSS and quality-of-life scores, were significantly better in the urethroplasty group. Complications were minor in both groups, with wound infections observed only after urethroplasty. Conclusion: Open urethroplasty offers superior long-term outcomes compared to endoscopic urethrotomy, with lower recurrence, better functional improvement, and higher patient satisfaction. Endoscopic urethrotomy may be considered for selected short strictures, but definitive urethroplasty should be prioritized in patients at high risk of recurrence. Keywords: anterior urethral stricture, endoscopic urethrotomy, open urethroplasty, recurrence, urinary flow, patient-reported outcomes.